Open Space, Human Resource, SDI The Analysis of Sport Open Space and Human Resource in Purbalingga Regency (Indonesian Journal for Physical Education and Sport, 2020)
The background of this research is to make a contribution to carry out development in the field of sports in Purbalingga Regency. In this study examines the availability of open space and the availability of sports human resources in Purbalingga Regency in terms of the Sport Development Index. The purpose of this study is to determine the availability of open space sports and the availability of human sports in terms of the Sport Development Index.This research uses a survey method through a quantitative approach. The research location is in the District of Purbalingga with the target of research is the District of Bukateja, District of Purbalingga and District of Bojongsari. The sampling technique uses stratified random sampling. The instrument of data collection is done by observation, interview and documentation. Data collection includes the amount of open space, the total population, the number of physical education teachers from elementary school through high school, trainers and sports structures. Then analyzed using the Sport Development Index of the availability of open space and sports human resources in order to get conclusions from existing phenomena.The results of the research into the availability of open sports are included in the middle category because open space is sufficient for the community, the availability of special fields in each village, many public facilities to exercise for the community. The availability of sports human resources falls into the low category due to the lack of sports trainers and instructors, not all certified physical education teachers, high population density.Conclusions in this study the availability of open space sports is sufficient with the middle category and the availability of sports human resources is still lacking in the low category in Purbalingga. Suggestions given by researchers are for the government of Purbalingga Regency to make programs concerning the development and improvement of the quality and quantity of sporting open spaces and the improvement of sports human resources.